Potencjał własny jednostek samorządu terytorialnego jako czynnik rozwoju lokalnego - Markowska-Bzducha, Ewa (The Own Investment Potential of the Local Government's Units as a Factor of Local Development, 2008)
The aim of this paper is to analyze own investment potential of local government in Poland. The survey was tarried out between 2003 and 2005 period. To achieve this aim, the analysis of own potential of the each groups of units was carried out The analysis demonstrated that in the surveyed period the potential means level, which local government could transferred to development purposes, increased. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 3, s. 339-347